Genetically based variation in heat tolerance covaries with climate in a globally important disease vector - Orlinick, Benjamin L.; Smith, Angela; Medley, Kim A.; Westby, Katie M. (Frontiers in Ecology and Evolution, 2024)
Vector-borne diseases (VBDs) are an increasingly important global health concern in the face of climate change. Understanding the ecology and evolution of vector species is critical to predicting and combating VBD. Vectorial capacity models, used to forecast disease transmission, traditionally assume traits are constant among populations, and little is known about whether different vector populations vary in thermal tolerance. To test for geographic variation in upper thermal tolerance, we determined the critical thermal maximum (CTmax) of Aedes. albopictus, a globally distributed mosquito and competent vector for many viruses including West Nile, chikungunya, and dengue. We studied CTmax for eight different populations spanning four climate zones across the Eastern United States. Using common garden experiments to isolate genetic variation, we found significant differences across populations for both adults and larvae, and these differences were more pronounced for adults. Larvae had higher CTmax values compared to adults. The differences between life stages likely result from different selection pressures experienced in their terrestrial and aquatic habitats. ToTo explore potential drivers of this variation we then tested the relationshipfor correlations between climatic variables measured near each population source and CTmax. Several climatic variables improved models CTmax for both adults and larvaeFor adult mosquitoes including, variance in the maximummean and max seasonal temperature, annual precipitation, and relative humidity all improved models of CTmax.For larvae, annual precipitation and relative humidity were important, as were average seasonal minimum temperatures. Annual precipitation appears to be particularly important and has a positive linear relationship with CTmax. The differences between life stages likely result from different selection pressures experienced in their terrestrial and aquatic habitats. Importantly, the assumption that mosquito populations within a species have the same upper thermal limits does not hold in this case, thus it is important to use population-specific CTmax values, among other important physiological parameters that may vary, to more accurately model and forecast VBDs.